Pengembangan Program Usaha Ekonomis Produktif dalam Pemberdayaan Perempuan di Kabupaten Sumenep - Rika Tini, Dwi Listia (Universitas Islam Malang, 2019)
This study aims to explain the Development of Productive Economic Business Programs in Sumenep Regency in the context of empowering women and improving the quality of women as development resources. The Development of Productive Economic Business Program is an effort of Sumenep Regency in order to build a better economy going forward related to the village economy. The method used in this study is a qualitative analysis method in which references are the basis for analysis. The Productive Economic Business Program Policy in Sumenep Regency is implemented under the auspices of the Community and Women's Empowerment Agency (BPMP) in the form of craftsmen business groups that utilize Natural Resources and Human Resources in each Village. This phase of UEP development activities is carried out through an empowerment process carried out over a period of 3 (three) years and the phasing plans are 1) First Year (2013), namely the Growth Stage; 2) Second Year (2014) Development Phase and 3) Third Year (2015) Independence Phase. From the UEP development activities that have a positive impact on women in rural areas, they can make money and help husbands without having to work far outside the home.